Financial versus Non-Financial Incentives for Improving Patient Experience - Thomas H. Lee MD, MSc (Journal of Patient Experience, 2015)
Delivering compassionate and coordinated care is a goal for all health care providers. Humans are not always consistent, though, both individually and collectively, and this is why everyone needs incentives to be at their best and to try to always be improving. The endlessly interesting question in patient experience is, what should those incentives look like? Should they be financial or nonfinancial? Dr. Thomas H. Lee explores what is most effective in regard to engaging and motivating physicians. While different approaches will work in different organizational cultures, financial incentives have their role in performance improvement. Compassionate coordinated care should be a social norm and be pursued by all health care organizations.